Addressing underestimated carbon monoxide emissions in Taiwan using CMAQ and impacts on local ozone concentration - Chieh-Sen Tsai; Ping-Chieh Huang; Hsin-Chih Lai; John C. Lin; Hui-Ming Hung (Atmospheric Environment: X)
Emission inventories play a crucial role in understanding and managing air quality. This research centers on carbon monoxide (CO), a low-reactivity species with a lifetime of 2 months, acting as a tracer for local pollutants. The investigation delves into the potential uncertainties within its emissions and the impacts. CO is significantly underestimated in the current air quality model using Taiwan Emission Data System 9.0 (TEDS 9.0) for Taiwan. The present CMAQ simulation underestimates CO in Taiwan by a factor of ∼3 compared to observations. With the minimum root mean square error (RMSE) analysis between simulation and observation, the optimal emission correction factors are estimated as 2, 4, and 3.6 for northern, central, and southern Taiwan, respectively. The simulated underestimation of CO concentrations, coupled with relatively consistent NOx concentrations compared to observations, might indicate possible uncertainties in emission sources, especially for sources with high CO/NOx ratios, such as vehicles. This discrepancy further suggests the possibility of underestimating other combustion chemical species, such as volatile organic compounds (VOCs), which are not adequately quantified in the ambient environment. Our findings indicate that the adjustment would increase local O3 concentration (up to 3 ppbv), with a minor decreased influence on NOx (less than 0.5 ppbv), underscoring the importance of accurate emission inventories in air quality modeling and the reassessment of the validity of CO and NOx emissions in a NOx-saturated environment. Our analysis of the potential emission sources highlights the importance of implementing stricter local emission controls and monitoring.